Las estrategias metodológicas que emplean los docentes de matemática y su incidencia en el desarrollo de destrezas con criterios de desempeño del bloque curricular de relaciones y funciones en los estudiantes de décimo año de educación general básica de la unidad educativa Ocho de Noviembre de la ciudad de Piñas, El Oro, durante el período lectivo 2013-2014. Lineamientos alternativos - Romero Rodas, Mayra Isabel (2014)
This research is a study on METHODOLOGICAL STRATEGIES USED MATH TEACHERS AND THEIR IMPACT ON THE DEVELOPMENT OF SKILLS WITH PERFORMANCE CRITERIA OF CURRICULUM AND FUNCTIONS BLOCK OF FOREIGN STUDENTS IN TENTH YEAR OF GENERAL EDUCATION BASIC EDUCATION UNIT EIGHT NOVEMBER PIÑAS CITY,GOLD, FOR THE PERIOD 2013-2014 LECTIVO. ALTERNATIVE GUIDELINES. The specific objectives are aimed at determining whether the methodological strategies used by teachers of mathematics affect the development of skills with performance criteria Curricular Relations and Functions block in students investigated Tenth Year of Basic General Education; assess how well the achievement level of skills and performance criteria in that curricular area and, depending on the results achieved by submitting an alternative methodological approach. The main results of the research are: Most teachers have not received training on methodological development of skills with performance criterion in curricular strategies Relations and Functions. All teachers considered that would improve aspects: cognitive, procedural and attitudinal students with Update and Curriculum Strengthening basic general education, as well as the development of skills with performance criteria in students. In the process of teaching- learning curricular Relations and Functions, most teachers and students surveyed claim that the art of problem solving and uses the descriptive class. Teachers agree that mental ability is a skill that can enhance student math performance. Students surveyed consider it important that teachers are trained permanently in curriculum planning and learning strategies for the development of skills with performance criteria, allowing them to participate actively in class. All teachers agree that to know whether students have acquired skills in their studies is to examine the curricular, problem solving without difficulty and conducting focus groups on the subject, where it stimulates job learning as a group, as well as asking questions of reasoning students to get to know the degree of learning that have been obtained in the curricular area.